Waste plastic bottle cap polypropylene (PP) as coarse aggregate replacement in concrete - Tan, Soon Teck (2015)
Polypropylene (PP) has been widely used by researchers to determine its performance in concrete matrix. Generally, PP will be crushed or reshaped into flakes, fibres or granular shapes. However, the cost and time consumption for processing will increased as the melting point of PP is around 170 oC. Hence, the novelty of this research was to determine the suitability of the polypropylene cap (without any alteration of shape) as coarse aggregate replacement in concrete. The results of slump test, rebound hammer test and compressive strength test shows that the PP cap were suitable to be replaced as coarse aggregate in concrete. The compressive strength of concrete with PP cap was 27.3 MPa, higher than 20 MPa which is suitable for general concrete work. Furthermore, the compressive strength results of concrete elevated to temperatures (100, 200, 300 and 600 oC) at the age of 28 days were also studied. From 100 oC to 300 oC, the results indicated that concrete with PP cap performed better than the control concrete. The coarse aggregate replaced by PP cap was fixed to 10 %. Based on the experimental results, It was concluded that the PP cap aggregates were suitable to replace as coarse aggregate in concrete